Integrated Global Estimation of Terrestrial Carbon Efflux - Yves Uwiragiye; Jing Wang; Yuanyuan Huang; Yuanyuan Huang; Yinfei Qian; Ahmed S. Elrys; Yi Cheng; Jianbin Zhou; Zucong Cai; Minggang Xu; Scott X. Chang; Christoph Müller (Global Change Biology, 2026)
Carbon efflux (C efflux ) makes up 20% of total greenhouse gases emitted globally. Accurate global C efflux is critical for projecting and responding to future global warming. However, current C efflux estimates remain incomplete due to the omission of C efflux released from the dissolution of inorganic carbon in calcareous soils (C efflux‐calcareous ) and dissolution of lime in acidic soils (C efflux‐acidic ). Here, we present a global terrestrial C efflux that incorporates C efflux‐calcareous , C efflux‐acidic , and soil respiration. Using 7562 field measurements from 2481 publications and machine learning, this study revealed that C efflux‐acidic and C efflux‐calcareous contributed 0.29% and 0.09%, respectively, to an overall C efflux of 96.52 Pg C year −1 (95% confidence interval, 91.2–101.9 Pg C year −1 ). Previous estimates of C efflux from soil respiration underestimated 0.4% of C efflux . Structural equation modelling (SEM) revealed that C efflux was directly driven by heterotrophic respiration, autotrophic respiration, dissolution of soil inorganic carbon and liming, while being regulated indirectly by land productivity (gross primary productivity, roots and litter), soil properties (soil acidity and soil inorganic carbon content), and anthropogenic activities (nitrogen fertiliser application). Soil acidification must be viewed as a dual challenge impacting both crop yields and global warming threats. Therefore, the study emphasises the need to incorporate neutralising soil acidity into soil carbon dynamics models, which was previously overlooked.